1999
DOI: 10.1111/j.1749-6632.1999.tb07893.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of FMRFamide‐related Peptides in Helminths

Abstract: Nervous systems of helminths are highly peptidergic. Species in the phylum Nematoda (roundworms) possess at least 50 FMRFamide-related peptides (FaRPs), with more yet to be identified. To date, few non-FaRP neuropeptides have been identified in these organisms, though evidence suggests that other families are present. FaRPergic systems have important functions in nematode neuromuscular control. In contrast, species in the phylum Platyhelminthes (flatworms) apparently utilize fewer FaRPs than do nematodes; thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 88 publications
(160 reference statements)
0
29
0
Order By: Relevance
“…Since then, FMRFamide and FMRFamide-related peptides have been isolated from a wide variety of invertebrate species, ranging from primitive metazoans, such as cnidarians, to higher invertebrates, such as insects (2)(3)(4)(5). FMRFamide-related peptides occur in all classes of cnidarians, suggesting that these peptides were among the first transmitters used in evolution (6).…”
mentioning
confidence: 99%
“…Since then, FMRFamide and FMRFamide-related peptides have been isolated from a wide variety of invertebrate species, ranging from primitive metazoans, such as cnidarians, to higher invertebrates, such as insects (2)(3)(4)(5). FMRFamide-related peptides occur in all classes of cnidarians, suggesting that these peptides were among the first transmitters used in evolution (6).…”
mentioning
confidence: 99%
“…Animals in which the coding region of the flp-7 and flp-11 peptide precursor genes has been deleted, neither display an observable phenotype [18]. However, in nematodes in particular, it has been reported that FaRPergic neurons innervate essentially all muscular systems [19]. In Ascaris suum, AMRNALVRFamide induces a shortening of the ovijector, coupled with an increase in contraction frequency [17].…”
Section: Discussionmentioning
confidence: 99%
“…The C. elegans genome (97 Mb, 19.099 genes in total) codes for about 1000 G-protein coupled receptors (GPCRs) [1]. About 100 of these encode neuropeptide GPCRs [2].…”
Section: Introductionmentioning
confidence: 99%
“…The conserved nature of the nematode nervous system means that physiological information gained from this species can be taken as representative of the phylum as a whole. The majority of FLPs tested in A. suum preparations potently modulate nerve and muscle activity in a concentration-dependent and reversible manner and this activity has been the subject of several reviews Geary et al 1999). For example, the FLP KHEYLRFamide produces a biphasic response resulting in increased contractility of body wall muscle at a threshold of 1 pM (Bowman et al 1996).…”
Section: F L P F U N C T I O N I N P L a N T P A R A S I T I C N E M mentioning
confidence: 99%